Is Tax Avoidance in the Mining Industry Moderated By Company Size - Desi Pratiwi Adhila Khoirunnisa; Putri Wulandari Hari Rachman; Puji Endah Purnamasari; Mardiana Mardiana (International Journal of Economics, Management and Accounting, 2024)
The goal of this study is to ascertain if tax avoidance is impacted by capital intensity, leverage, and profitability which is moderated by firm size. Purposive sampling is used for the sample in this study, which focuses on mining companies that are listed on the IDX. The websites of the respective companies and IDX were used to get the data. The data were analyzed using MRA and multiple linear regression. The results demonstrate that while profitability and capital intensity have a significantly positive impact on tax avoidance, leverage has a negative impact. This study also demonstrates that firm size can moderate the impact of capital intensity and leverage, but it cannot moderate the impact of profitability.